2019
DOI: 10.1016/j.aninu.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Laying hen performance, egg quality improved and yolk 5-methyltetrahydrofolate content increased by dietary supplementation of folic acid

Abstract: This study was performed to evaluate the effect of folic acid (FA) on performance, egg quality and yolk 5-methyltetrahydrofolate (5-MTHF) content. A total of 384 Hy-line W36 strain hens from 52 to 58 weeks of age were randomly assigned to 4 groups, and each group received one of following dietary treatments: 0, 5, 10 and 15 mg FA/kg diet. A completely randomized design was used. Egg production percentage, egg mass and egg weight were increased significantly ( P < 0.05) and feed conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(41 reference statements)
3
9
0
Order By: Relevance
“…Our results showed less damage on the eggs washed by PAW than on the commercially washed eggs. The egg cuticle, which comprises several layers, is closely associated with egg freshness (Bagheri et al, (2019)) [18]. Thus, less damage to the cuticle usually indicates a lower loss of egg quality during storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed less damage on the eggs washed by PAW than on the commercially washed eggs. The egg cuticle, which comprises several layers, is closely associated with egg freshness (Bagheri et al, (2019)) [18]. Thus, less damage to the cuticle usually indicates a lower loss of egg quality during storage.…”
Section: Discussionmentioning
confidence: 99%
“…All eggs were stored at room temperature, and the freshness of the eggs was determined on the testing day (Day 0), as well as 7 and 14 days after treatment. Egg freshness was determined based on the procedures described by Bagheri et al (2019) [18].…”
Section: Methodsmentioning
confidence: 99%
“…Sufficient content of essential amino acid and balance amino acid composition played an extremely important role in the nutritional value and edible flavor of food ( Wu et al, 2013 ). Many studies showed that the nutrition and flavor of eggs were affected by factors such as dietary nutrients and feeding methods ( Perić et al, 2011 ; Bashir et al, 2015 ; Dong et al, 2018 ; Bagheri et al, 2019 ). The tender stems and leaves of ramie contained high level of crude protein.…”
Section: Discussionmentioning
confidence: 99%
“…Egg yolk has a good potential for enrichment by the supplemented diets with different minerals and vitamins. It is possible to significantly increase vitamin content of eggs through fortification of the laying hen diet with synthetic vitamins, and table eggs can be changed to one of the rich sources of natural synthetic microelements [20][21][22][23][24][25][26]. The cobalt is not considered as an essential mineral for hens even though it may consist as much as 4% of the composition of the molecule of vitamin B 12 .…”
Section: Discussionmentioning
confidence: 99%